China's Non-Western Soft Power Policy In Establishing A New Order: A Review Of Strategy And Resources - Ali, Hemn Shawkat (JURNAL TAPIS, 2023)
State power, in the modern era, is not just based on the concepts of political, military, and economic efficiency. The rise of the era of globalization and the interaction and interdependence of state in the international system has led to the centralization of a new concept known as "soft power". Soft power is the frame of attraction and a fundamental tool of influence for states that can be attained without using military intervention and prowess. The soft power strategy was primarily developed by Professor Joseph Nye, and the West rationally employed it as a political approach to portray and establish the face of their liberal hegemony. In the last few years, China has made significant efforts to enhance its soft power capabilities. It is observed that the liberal face of the West is declining. As a result, new active manifestations are emerging from the East, especially from China. The paper argues that China attempts to change its historical perception of how to interact with states on a global scale by resorting to Western soft power, such as relying on cooperation policies with many countries. The study examines China's soft power strategy; in doing so, it aims to highlight China's soft power strategy compared to Western soft power. In order to better understand how China interprets soft power and its resources, this study assesses whether China represents a new approach to identifying its "soft power" concept.